Understanding the effect of refractory metal chemistry on the stacking fault energy and mechanical property of Cantor-based multi-principal element alloys - Singh, Prashant; Trehern, William; Vela, Brent; Sharma, Prince; Kirk, Tanner; Pei, Zongrui; Arroyave, Raymundo; Gao, Michael C.; Johnson, Duane D. (International journal of plasticity, 2024)
•Elemental role on plasticity and strength from first-principles calculations.•Unraveled role of alloying refractory metals in SFE of FCC high entropy alloys through combinatorial CALPHAD and first-principles calculations.•Minimal variation in concentration of refractory element is sufficient to tune SFE in FCC alloys.•Ni60Fe5Cr5Co5Nb25 show a high yield strength of 1069 MPa as well as high pugh's ratio of 2.33, overcoming an impasse of strength ductility trade-off. Multi-principal-element alloys (MPEAs) based on 3d-transition metals show remarkable mechanical properties. The stacking fault energy (SFE) in face-centered cubic (fcc) alloys is a critical property that controls underlying deformation mechanisms and mechanical response. Here, we present an exhaustive density-functional theory study on refractory- and copper-reinforced Cantor-based systems to ascertain the effects of refractory metal chemistry on SFE. We find that even a small percent change in refractory metal composition significantly changes SFEs, which correlates favorably with features like electronegativity variance, size effect, and heat of fusion. For fcc MPEAs, we also detail the changes in mechanical properties, such as bulk, Young's, and shear moduli, as well as yield strength. A Labusch-type solute-solution-strengthening model was used to evaluate the temperature-dependent yield strength, which, combined with SFE, provides a design guide for high-performance alloys. We also analyzed the electronic structures of two down-selected alloys to reveal the underlying origin of optimal SFE and strength range in refractory-reinforced fcc MPEAs. These new insights on tuning SFEs and modifying composition-structure-property correlation in refractory- and copper-reinforced MPEAs by chemical disorder, provide a chemical route to tune twinning- and transformation-induced plasticity behavior. [Display omitted]